Studying of Biological Activity of Fraction Less Than 5 kD From Cattle Cord Blood Cryohaemolizate - Gulevskiy, A. K.; Moiseyeva, N. N.; Abakumova, Ye. S.; Nikolchenko, A. Yu.; Shchenyavkiy, I. I.; Gorina, O. L.; Trifonova, A. V.; Ivanov, Ye. G. (Problems of Cryobiology and Cryomedicine, 2008)
The wound and ulcer healing and sugar-decreasing activities of the fraction less than 5 kD derived from the cord blood cryohaemolizate has been investigated. Stimulating effect of this cord blood fraction on phagocytic and proliferative activities of cells was discovered under in vitro conditions. By means of gel-penetrating chromatography and biochemical tests it has been shown that the pattern of cord blood fraction low molecular substances is different from the Actovegin pattern both qualitatively and quantitatively.